Effect of a Safety Leadership Training Including Coaching on Safety Performance and Climate in Wood-processing Companies - Kwangsu Moon (Elsevier, 2024)
Background: The wood-processing industry has historically exhibited high rates of occupational hazards resulting in illness and injury. One of the major causes of high injury rates is small firm size, as resource constraints generally preclude hiring safety officers. This study examined the effect of a safety leadership training program that included coaching for managers on workers' safety behaviors and safety climate in three wood-processing companies. Methods: One or two managers at each site participated in this study. The manager training consisted of safety leadership education, safety observation, positive or corrective feedback on workers' behaviors, goal setting, and low-cost rewards for meeting goals. The dependent variable was the percentage of safe employee behaviors recorded on a critical behavior checklist developed for this study. Safety climate was measured before and after the intervention. An AB multiple baseline design across settings was adopted. After the baseline (A), the training program (B) was introduced to each site at different points in time. Results: After the introduction of safety leadership training, the mean rate of safety compliance increased by 15.3%, from 80.38% to 95.68%, and safety climate scores increased significantly from an average of 3.2 to 3.47. Conclusion: These results suggest that safety leadership coaching can be effective in improving safety management in small sawmilling sites. Implications, limitations, and possible future research directions are discussed.